Modelo de gestión de recursos humanos y la rotación de personal de la Empresa Adecco Perú S.A. - Oficina Cartavio 2014. - Vasquez Rebaza, Oscar Alexander (2014)
This research work was developed with the purpose of developing a model of human resources management and the turnover of the company's "Adecco Peru S.A-Office Cartavio 2014." With the determination of this work, the company will emphasize the most relevant points in which not is is working properly, allowing a performance right within the organization. This research report was descriptive design - transactional, statistical; and a survey as a research technique was applied.In the surveys applied to the staff of the company "ADECCO PERU S.A-Office CARTAVIO, we can highlight that a human resources management model allows reducing significantly the rotation of personnel of the company Adecco S.A.-Office Cartavio." In addition with the design and implementation of a definite well plan of quality of attention, the company will be able to determine the needs of service that satisfy the clients, to announce the perceptions and expectations of the clients on the quality in the service that they receive, in order that hereby the Restaurant could evaluate and fulfill with major efficiency his aims of quality. As a conclusion the incorporation of a new model of administrative management proposes preliminary and thorough evaluation of the current situation, so as to know each and every one of the administrative processes developed within the institution and the elements involved in them, both personal and material.